First bryophyte records from Diego Ramírez Archipelago: Changing lenses in long-term socio-ecological research at the southernmost island of the Americas - Bernard Goffinet; John J. Engel; Matt von Konrat; Mackenzie Calderon, Roy; Contador Mejias, Tamara Andrea; Sebastián Rosenfeld; Omar Barroso; Rozzi Marin, Ricardo Roberto (My University, 2020)
Long-term socio-ecological research requires comprehensive assessments of biodiversity that overcome historical taxonomic biases, such as the strong focus on the vascular flora. This is particularly relevant at high latitudes where the richness of non-vascular plant species exceeds that of vascular species. Additionally, with respect to geographical regions, there is also a marked bias towards ecological and conservation research in the northern hemisphere. In contrast, few studies have investigated patterns of non-vascular species richness in relation to conservation priorities at sub- Antarctic latitudes, particularly in the sub-Antarctic Magellanic ecoregion. In this work, we contribute to overcome such taxonomic, geographical and ecoregional biases by moving outside these limits, and therefore â changing the lensesâ that are commonly used to assess and conserve biodiversity. We implemented these new â biocultural lensesâ by including, for the first time, bryophytes in the floristic inventory of the southernmost island of the American continent: Gonzalo Island (56Â°31â 16.8â â S; 68Â°42â 53.5â â W) in the Diego RamÃrez Archipelago, Chile. The first bryological exploration of the Diego RamÃrez archipelago, SW of Cape Horn, revealed a bryophyte flora composed of 14 species, eight liverworts and six mosses. This number of non-vascular plant species almost doubles the eight vascular plants present on the island. Consequently, with our study, we aim to fill a critical gap in the knowledge of the flora of the Diego RamÃrez archipelago, and establish an integral floristic characterization for the long-term socio-ecological research and conservation of the southernmost archipelago of South America. Based on the field material collected, the new nomenclatural combination Chiloscyphus secundifolius (Hook. f. & Taylor) J.J.Engel is proposed. The moss flora comprises Amblystegium serpens, a widespread moss, yet hitherto unknown for sub-Antarctic Chile. The bryoflora of Diego RamÃrez has its greatest affinities with that of the sub-Antarctic Magellanic ecoregion and Maritime Antarctica. None of the liverworts present on Gonzalo Island occurs on continental Antarctica; in contrast, four of the six mosses are shared between these two areas.
Keywords: Archipelago; Vascular plant; Bryophyte; Floristics; Flora; Lejeuneaceae; Endemism; Phytogeography